The Effectiveness of Yoga Exercise to Reduce Blood Sugar Levels in Diabetes Mellitus Sufferers - Sriwahyuni, Sriwahyuni; Darmawan, Sri; Nurdin, Sulkifli; Allo, Olgrid Algarini; Hasifah, Hasifah (Qualitative and Quantitative Research Center, 2023)
Diabetes Mellitus (DM) is considered scary because it is chronic and leads to complications from other serious diseases. However, the good news is that DM can be prevented and controlled. The heart, blood vessels, kidneys, eyes, nerves, and other organs can become involved. Therefore, non-pharmacological (lifestyle modification) control of physical activity is necessary to manage DM. One solution is yoga practice. This research aims to determine the effectiveness of yoga exercises in reducing blood sugar levels in diabetes mellitus sufferers. This research design is an analytic experiment with a quasi-experimental design using a non-equivalent control group approach and involving a control group not treated with the same pre and post-treatment samples (paired samples). A sample of 24 people. The research location is Tamalanrea Community Health Center, Makassar, Indonesia. The results showed a significant difference in GDS levels before and after yoga exercise. This is supported by the mean value of GDS levels, which decreased 74.25 mg/dL after yoga exercise. The correlation strength of the intervention is 0.965, so it can be said that yoga exercise is powerful in reducing GDS levels in DM patients. It was concluded that there was a significant difference in GDS levels before and after yoga exercise. The research contribution is recommended to provide education to patients with Diabetes Mellitus Type 2 to increase physical activity as a way of non-pharmacological therapy to keep blood sugar levels in a normal state.